Aims of Education in Hadist - Ilham Adiansyah Harahap; Ahmad Rifai; Irwansyah Jul; Zulfahmi Lubis (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Islamic religious education is the most important thing in the education system in Indonesia. Because Islamic religious education is education that contains moral, intellectual and spiritual education. Islamic education has goals that are based on religious teaching sources, one of which is the hadith. Hadith is the second source of guidance after the Koran in Islam. The results of this article are the definition of education, the goals of education in Islam, and the goals of education in the hadith. The purpose of this writing is to examine the objectives of Islamic education contained in the Hadith of the Prophet SAW.